2018
DOI: 10.1590/1983-21252018v31n105rc
|View full text |Cite
|
Sign up to set email alerts
|

Diallel Analysis of Tolerance to Drought in Cowpea Genotypes

Abstract: The low use of technologies by farmers and the occurrence of biotic and abiotic stresses are limiting factors for cowpea production in the Brazilian Northeast region. The tolerance of genotypes to drought is an alternative to decrease the negative effects of stresses on cowpea production. Thus, the objective of this work was to identify parents and combinations of cowpea genotypes with high probability of generating segregating populations with tolerance to drought. Six cowpea genotypes were crossed in a compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 13 publications
3
16
0
1
Order By: Relevance
“…According to the average seed yields in the F2 generation, the parental values varies between 17.04 g/plant (Karagöz) and 52.06 g/plant (Sırma), and in the F2 generation, the single-plant seed yields were 24.45 g/plant (Sırma x Karagöz) and 51.41 g/plant (Pekşen x Karagöz) (Table 6). With the findings of this study, Ceyhan (2004), Peksen and Artık (2004), Ceyhan et al (2008), Borivoj et al (2013), Kadam et al (2013), Ceyhan et al (2014), Rodrigues et al (2018), Walle et al (2019), andJoshi et al (2022) are in harmony.…”
Section: Seed Yield Per Plantsupporting
confidence: 68%
See 2 more Smart Citations
“…According to the average seed yields in the F2 generation, the parental values varies between 17.04 g/plant (Karagöz) and 52.06 g/plant (Sırma), and in the F2 generation, the single-plant seed yields were 24.45 g/plant (Sırma x Karagöz) and 51.41 g/plant (Pekşen x Karagöz) (Table 6). With the findings of this study, Ceyhan (2004), Peksen and Artık (2004), Ceyhan et al (2008), Borivoj et al (2013), Kadam et al (2013), Ceyhan et al (2014), Rodrigues et al (2018), Walle et al (2019), andJoshi et al (2022) are in harmony.…”
Section: Seed Yield Per Plantsupporting
confidence: 68%
“…Heterosis values varied between -29.23% (Sırma x Karagöz) and 131.55% (Pekşen x Karagöz), and heterobeltiosis values ranged between -53.03% (Sırma x Karagöz) and 87.83% (Pekşen x Karagöz) (Tables 7 and 9). In their previous studies, Kadam et al (2013), Magar et al (2016), Gupta et al (2017), Rodrigues et al (2018), Owusu et al (2020), andJoshi et al (2022) reported that heterosis was more significant than herobeltiosis in seed yield.…”
Section: Seed Yield Per Plantmentioning
confidence: 95%
See 1 more Smart Citation
“…These genotypes are the best suitable parents used for further breeding programs (Carvalho et al 2019). Some breeding to improve drought tolerance is directed to a diallel analysis (Rodrigues et al 2018) and genetic architecture for grain yield, biomass, and delayed senescence (Muchero et al 2013). Hall (2004) based on the results of their studies of cowpea breeding to heat stress reviewed that breeding for heat stress adaptation directed on crop phenology, heat tolerance during reproductive development, and interactions between heattolerant during reproductive development and other traits.…”
Section: Cowpeasmentioning
confidence: 99%
“…Trotter] (Abraha et al., 2018), coriander ( Coriandrum sativum L.) (Gholizadeh et al., 2018), cowpea [ Vigna unguiculata (L.) Walp.] (Rodrigues, Damasceno‐Silva, Rocha, Bastos, & Santos, 2018), Indian mustard ( Brassica juncea L.) (Singh, Kumar, Kaur, Singh, & Kaur, 2019), and sunflower ( Helianthus annuus L.) (Abdelsatar, Elnenny, & Hassan, 2020).…”
Section: Introductionmentioning
confidence: 99%